2017
DOI: 10.1016/j.jctb.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing highly edge-connected graphs into paths of any given length

Abstract: Abstract. In 2006, Barát and Thomassen posed the following conjecture: for each tree T , there exists a natural number k T such that, if G is a k T -edge-connected graph and |E(G)| is divisible by |E(T )|, then G admits a decomposition into copies of T . This conjecture was verified for stars, some bistars, paths of length 3, 5, and 2 r for every positive integer r. We prove that this conjecture holds for paths of any fixed length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
(21 reference statements)
2
23
0
Order By: Relevance
“…In particular, our proof of Theorem 1.3 yields a third proof of the path case of Conjecture 1.1. It is also important mentioning that this proof is, in terms of approach, quite different from the one from [2].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In particular, our proof of Theorem 1.3 yields a third proof of the path case of Conjecture 1.1. It is also important mentioning that this proof is, in terms of approach, quite different from the one from [2].…”
Section: Introductionmentioning
confidence: 82%
“…Thomassen then proved, in [13], the conjecture for arbitrarily long paths of the form P 2 k . Later on, Botler, Mota, Oshiro and Wakabayashi proved the conjecture for P 5 [3] before generalizing their arguments and settling the conjecture for all paths [2]. Conjecture 1.1 being now solved, many related lines of research sound quite appealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and by Hang(v, B) the number of edges leaving v in O i.e., Hang(v, B) = d + O (v) . We say that an edge that leaves v in O is a hanging edge at v (this definition coincides with the definition of pre-hanging edge in [1]). We say that a tracking decomposition…”
Section: Notationmentioning
confidence: 99%
“…Since Thomassen's paper [16], which shows that 171-edge-connected graphs of size divisible by 3 can be decomposed into paths of length 3, there has been considerable interest in path decompositions of highly connected graphs (also see [17]). In [4] it is shown that for any fixed length k, there is a constant C(k) such that any C(k)-edge-connected graph G has a decomposition into paths of length k if and only if k divides the size of G.…”
mentioning
confidence: 99%